2022
DOI: 10.1002/pmrj.12827
|View full text |Cite
|
Sign up to set email alerts
|

Association between landing biomechanics, knee pain, and kinesiophobia in athletes following anterior cruciate ligament reconstruction: A cross‐sectional study

Abstract: Introduction: Kinesiophobia is a fear of physical movement and activity and is known to affect return to sports and second injury after anterior cruciate ligament reconstruction. Objective: To determine the association among landing biomechanics, knee pain, and kinesiophobia in athletes following anterior cruciate ligament reconstruction. Design: A cross-sectional study. Setting: Clinical center of sports medicine. Participants: This study included 31 athletes who participated in sports after primary, unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The level of sport participation varied in the 14 studies included in the review. In one study, the authors examined adolescent athletes [ 20 ], three examined high-school and/or collegiate athletes [ 21 , 22 , 23 ], one examined professional athletes [ 24 ], two examined recreational athletes [ 5 , 25 ], and seven examined a combination of levels [ 11 , 16 , 26 , 27 , 28 , 29 , 30 ], such as recreational and collegiate athletes. The athletes played diverse sports, including running [ 25 ], football and lacrosse [ 21 ], alpine skiing [ 24 ], and various college sports, including baseball, basketball, futsal, gymnastics, lacrosse, soccer, softball, table tennis, tennis, and track and field [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of sport participation varied in the 14 studies included in the review. In one study, the authors examined adolescent athletes [ 20 ], three examined high-school and/or collegiate athletes [ 21 , 22 , 23 ], one examined professional athletes [ 24 ], two examined recreational athletes [ 5 , 25 ], and seven examined a combination of levels [ 11 , 16 , 26 , 27 , 28 , 29 , 30 ], such as recreational and collegiate athletes. The athletes played diverse sports, including running [ 25 ], football and lacrosse [ 21 ], alpine skiing [ 24 ], and various college sports, including baseball, basketball, futsal, gymnastics, lacrosse, soccer, softball, table tennis, tennis, and track and field [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The athletes played diverse sports, including running [ 25 ], football and lacrosse [ 21 ], alpine skiing [ 24 ], and various college sports, including baseball, basketball, futsal, gymnastics, lacrosse, soccer, softball, table tennis, tennis, and track and field [ 23 ]. Most studies examined athletes who had anterior cruciate ligament or other knee injuries [ 16 , 24 , 25 , 26 , 27 , 28 , 29 ], or ankle injuries [ 5 , 21 , 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [8,23,48] deined high kinesiophobia using the TSK as a score of greater than 37. Two studies [38,39] used TSK-11 to correlate high levels of kinesiophobia as having a score greater than 17. At 4-8 weeks, 62% of ACLR patients experience kinesiophobia with 43.1% and 30.8% experiencing high kinesiophobia at 3 and 12 months postoperatively, respectively [48].…”
Section: Deining Fear Of Reinjurymentioning
confidence: 99%
“…TKA patients who are not mobilized may develop an ever‐increasing fear of standing up and moving in a short time, and they may think that mobilization may cause another injury and increase the severity of the pain they feel. Therefore, TKA patients are considered a patient profile suffering from kinesiophobia, which is a pathological fear that is characterized by the excessive avoidance of physical movement and activity 6–8 . The incidence of kinesiophobia following orthopaedic trauma was reported to reach up to 52.8% 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TKA patients are considered a patient profile suffering from kinesiophobia, which is a pathological fear that is characterized by the excessive avoidance of physical movement and activity. [6][7][8] The incidence of kinesiophobia following orthopaedic trauma was reported to reach up to 52.8%. 9 Another study revealed that in TKA patients, kinesiophobia affected knee flexion range of motion, performance in the 2-min walk test, and pain severity in the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%